INFLUENCE OF VARIETAL CHARACTERISTICS ON THE YIELD OF CARROT ROOTS IN THE CONDITIONS OF THE EASTERN FOREST-STEPPE - Pidlubenko , І.; Konovalenko , К.; Horash , О.; Klymyshyna , Р. (Bulletin of Lviv National Environmental University. Series Agronomy, 2025)
One of the most significant challenges in modern vegetable cultivation is enhancing the yield and quality of carrot roots by optimizing varietal selection based on the soil and climatic conditions of each growing area. In Ukraine's Eastern Forest-Steppe, where climatic factors can vary greatly, it is particularly crucial to identify carrot varieties that consistently deliver high yields while maintaining excellent marketable qualities. Although there is an extensive range of varieties available in the state register, practical vegetable growers often struggle to select the most suitable and productive options. The objective of our research was to identify carrot varieties that are optimally adapted to the growing conditions in the Eastern Forest-Steppe region and can provide high productivity levels. Field research was conducted between 2022 and 2023 on podzolized medium loamy chernozem at the laboratory of biennial and rare crops selection at the Institute of Vegetable and Melon Growing of NAAS. The varieties examined included Yaskrava (control), Naryna, Svytshan, and Hreta. Biometric observations revealed that the Hreta variety produced the highest number of leaves (12) and had the largest rosette diameter (42 cm). In terms of yield, Svytshan (55.3 t/ha) and Hreta (62.3 t/ha) significantly outperformed the control variety Yaskrava (45.1 t/ha) by 10.2 and 17.2 t/ha, respectively. These results indicate the high productivity and adaptability of Svytshan and Hreta varieties in the conditions of the Eastern Forest-Steppe. We have established the importance of introducing these varieties into production to enhance the efficiency of the vegetable industry and bolster food security in the region. The findings of this study enable more rational variety selection, optimizing sowing practices and increasing the stability and competitiveness of carrot production.